Assessment of total soil contamination with heavy metals in the coastal area of the cape peschany (Eurasian Journal of Ecology, 2019)
In the autumn of 2018, in the coastal zone of the Caspian region, namely, in the area of Cape Peschany, scientific field studies of the state of the soil were carried out. 7 test sites (TS) were investigated.Studied more than 30 soil samples taken from depths of 0-5 and 5-20 cm spectrophotometer laboratoryHACH DR-2400 (USA) determined the total contents of heavy metals (HM). For analyz ephase threetotal soil pollution (TSP) or TS, using different approaches, the used value of the content of chemicalelements in the background area TS-the background. The soil of the Karakia-Karakol reserve was used asa background. Only the value of KC>1 was taken into account in the calculation of ZC. Perhaps in thisregard, for TS-3 (garden), the lowest total soil pollution index was obtained, including negative valuesof ZC(r). The results of the calculations, only on TS-2, ZСТ=16.5 level of contamination moderate threaton the remaining TS and within the acceptable level. Statistical processing of the results in the programStatistica 10 showed that the criterion of Kruskal-Wallis is statistically significant for the elements of Cr,Cd, Cu and Co.Key words: Caspian Sea, Cape Peschany, soil, heavy metals, total pollution.